Financial Performance and Company Value: Systematic Literature Review - Argianov Ramadhan; Enggar Diah Puspa Asum; Wiralestari (Cita konsultindo, 2025)
This article aims to conduct a systematic literature review of empirical and theoretical studies in the last five years (2020–2024) which discuss the relationship between financial performance and company value in various countries. This research summarizes the most commonly used financial performance indicators, such as ROA, ROE, EPS, and NPM, and evaluates their contribution to company value. In addition, this article analyzes the consistency and variation of research results based on methodology, geographic location, industry type, and theoretical approaches such as signal, agency, and stakeholder theory. The literature selection process is carried out through leading databases (Scopus, Web of Science, Pro Quest) with certain inclusion criteria. The results of the review show that internal factors such as CSR, ESG, green innovation, and risk management generally have a positive influence on company performance and value, depending on the context in which they are applied. It is hoped that this article will become a critical and useful reference for future researchers in developing similar studies.